Analysis of E-Exam practices in higher education institutions of KSA: Learners' perspectives. (November 2022) - Gokulkumari, G.; Al-Hussain, Thamer; Akmal, Syed; Singh, Prakash
Highlights: COVID-2019 becoming worldwide in 2020, many of innovations have constantly served the improvement of educational process. In the twenty-first century, the E-Exam has profited as the test-takers are accustomed to seeing and using new technology. The technology saves cost, prevents hand-writing and student identification bias, and reduces impact of student mistakes. But still, there are inconveniences, like inter operativeness, which can jeopardize the reliability of answers of students. Many studies show that E-Exams are well-liked by students and have a favorable impact on teacher evaluations. Abstract: Assessment is an important aspect of learning. It is done to find out what each student learned. The adoption of valid assessment techniques will help to improve the quality of the educational process. It will allow students to determine whether or not they achieved their learning goals. Due to this importance, students are assessed in a variety of ways. E-Exams are an example of such a technique. Students in university courses must be examined in a short period through mid-examinations and final exams. This necessitates the use of a quick evaluation procedure to yield rapid results. This research work aims to analyze the student perceptions towards the E-Exam system in higher education in Saudi Arabian universities. The study of the E-Exam system is primarily focused on the following subjects: (a) E-Exam implementation (b) E-Exam environment Factors (c) Student Experience Based on E-Exam Attempts (d) E-Exam System Challenge. (e) Recommendations for E-Exam requirements. The suggested work is divided into three stages: The first step begins with the preparation of a questionnaire that has explicitly addressed the impact of the aforementioned motivations on learners. The data presented in the questionnaire were intimately associated with KSA university students. The developed questionnaire was distributed to students as well as research scholars at KSA universities in the second phase. All of the questions in the questionnaire are made mandatory to fill. In the third step, the responses of concerned individuals from Saudi Arabian universities are analyzed. The evaluation has been made with ANOVA and SEM analysis.